Spacers to Improve Performance and Porosity of Graphene Based Polymer Electrolyte Fuel Cells. (8th September 2020) - Suter, Theo; Clancy, Adam; Rubio Carrero, Noelia; Heitzmann, Marie; Guetaz, Laure; Shaffer, Milo; Howard, Christopher A.; McMillan, Paul F.; Brett, Dan
Abstract : Graphene has been suggested as a potential support material to replace commercial carbon black due to its carbon corrosion resistance. However, graphene-based electrodes typically perform poorly in MEA testing due to restacking of the graphitic sheets. In this study we investigate the introduction of carbon black and their effects on the porosity and current density of graphene-based supports.